Thermal Properties of the Very Low Thermal Conductivity Ternary Chalcogenide Cu4Bi4M9 (M = S, Se). Issue 8 (26th May 2020) - Hobbis, Dean; Wang, Hsin; Martin, Joshua; Nolas, George S.
Abstract : Temperature‐dependent thermal properties of phase‐pure polycrystalline ternary chalcogenides Cu4 Bi4 S9 and Cu4 Bi4 Se9 are reported. The structure and bonding in these materials result in very low thermal conductivity values (<0.8 W m −1  K −1 at room temperature) for both materials. The lattice contribution, Debye temperatures, and Sommerfeld coefficient are obtained from low‐temperature heat capacity data that also indicate very small electronic contributions to the heat capacity for these materials. This study aids in the identification of new nontoxic, earth‐abundant resistive ternary chalcogenide materials with low thermal conductivity for potential thermal barrier coating and rewriteable storage applications. Abstract : Analyses of the thermal properties of Cu4 Bi4 M9, with M = S, Se, are reported. The temperature‐dependent thermal properties illustrate the anharmonicity in these materials, resulting in very low thermal conductivity. This report is aimed to further understanding of the fundamental properties of these chalcogenide materials, as they continue to be of interest for a variety of applications.